2005
DOI: 10.1152/japplphysiol.00910.2003
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanics of canine internal abdominal muscles

Abstract: The internal abdominal muscles are biaxially loaded in vivo, and therefore length-tension relations along and transverse to the directions of the muscle fibers are important in understanding their mechanical properties. We hypothesized that 1) internal oblique and transversus abdominis form an internal abdominal composite muscle with altered compliance than that of either muscle individually, and 2) anisotropy, different compliances in orthogonal directions, of internal abdominal composite muscle is less prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 19 publications
(21 reference statements)
3
21
0
Order By: Relevance
“…The in vitro stress-strain relationships obtained in this study showed similar nonlinear patterns to those previously published for soft tissues in general, also undergoing large deformations (Quapp and Weiss, 1998;Davis et al, 2003;Hwang et al, 2005;Lopez et al, 2008;Calvo et al, 2009). The results of the in vitro experiments showed that the strain level at which the muscle stress began to increase rapidly for increased strain levels was around 20%, while for the tendon it was around 5%, coinciding with Hawkins and Bey (1997).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The in vitro stress-strain relationships obtained in this study showed similar nonlinear patterns to those previously published for soft tissues in general, also undergoing large deformations (Quapp and Weiss, 1998;Davis et al, 2003;Hwang et al, 2005;Lopez et al, 2008;Calvo et al, 2009). The results of the in vitro experiments showed that the strain level at which the muscle stress began to increase rapidly for increased strain levels was around 20%, while for the tendon it was around 5%, coinciding with Hawkins and Bey (1997).…”
Section: Discussionsupporting
confidence: 85%
“…Very few studies have tested muscle samples from different animals; for instance, canine (Hwang et al, 2005) and porcine muscle (Van Loocke et al, 2006) specimens were tested passively while Lopez et al (2008) tested mice specimens both passively and actively. To the authors' knowledge, there is no study including all the steps described above carried out upon the same specimen.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, many studies only focused on the response of some components of the abdominal wall using an ex vivo sample testing approach. For example, Hwang et al (2005) and Hernández et al (2011) studied the behaviour of the abdominal muscles on animals. Some authors conducted tensile tests on the human linea alba and rectus sheath (Rath et al 1997;Hollinsky and Sandberg, 2007;Förstemann et al, 2011;Martins et al, 2012;Ben Abdelounis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the abdominal muscles seem less frequent and did not include human samples. Nilsson (1982) and Hernández et al (2011) characterized rabbit abdominal muscles while Hwang et al (2005) tested dog lateral abdominal muscles (obliquus externus abdominis, obliquus internus abdominis and transversus abdominis). The results reported in the literature were found to be different from one component to another and show high variations and standard deviations.…”
Section: Introductionmentioning
confidence: 99%